Sustainable Quality Management Systems in Cosmetics: Integrating Green Chemistry and Circular Manufacturing - SOWMYA; Dr. KELLA ALEKHYA S; Dr. MANIMARAN (The Bioscan, 2025)
The entire cosmetic industry undergoes a transformation toward sustainability, with consumers becoming increasingly aware, the market acquiring heavier regulations, and increasing global concerns over the environment. This paper treats Sustainable Quality Management Systems in the cosmetic sector, especially on the synergic interaction between green chemistry and circular manufacturing. Existing QMS models often do not take into account long-term ecological impacts. Hence, there is a need for quality systems precious for product safety and also that look into ethical sourcing and environmental impacts. Such consideration on international regulatory compliance systems with utmost transparency is illustrated through ISO 22716 and the Indian Drugs and Cosmetics Act in the sustainable product development method. Aspects of green chemistry ranging from the prevention of waste, atom economy, and less hazardous chemical syntheses to using renewable feed stocks are evaluated in relation to raw material selection, product formulation, and risk assessment. On the other hand, circular economy strategies put to evaluation are reuse, recycle, and closed-loop supply chain, with case studies provided in reference to prominent players like L’Oreal. The findings point out that cosmetic manufacturers need to implement holistic quality systems with sustainability linked to them so that it can form a basis for competitive advantage and long-term ecological stewardship.